Peran Guru Ngaji dalam Meningkatkan Kemampuan Membaca Al-Quran di Masyarakat Pedesaan: Studi Kasus di Desa Simbagwetan Kabupaten Pekalongan - Fitriyani, Ina; Aini, Rofiqotul (TSAQOFAH, 2024)
The role of the Koran teacher in improving reading of the Koran is very important, because the Koran teacher's job has a big influence on the learning process. As a Koran teacher, you must always be able to master the learning material being taught and develop yourself in the sense of improving your skills in relation to existing knowledge. Because these things really determine the learning outcomes that students must achieve. Basically, the role of a Koran teacher is the same as a school teacher, but Koran teachers have a certain schedule which is determined based on an agreement with parents, which is different from state schools which have a special schedule. This type of research is field research using data collection methods in the form of interviews, observation and documentation. The results of this research show that teachers play a very important role in improving the ability to read the Al-Quran, especially in Simbangwetan Village. The role of the Koran teacher is as a teacher, as an educator and as a leader.